IMPLEMENTASI PROGRAM SEKOLAH PENGGERAK (PSP) TAHUN 2021 DI SDN 23 MENYUMBUNG KABUPATEN SINTANG, KALIMANTAN BARAT - Jumardi Budiman; Muhammad Irfan; Tira Maya Maisesa Malino (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2022)
The purpose of this study is to describe the implementation of the “Program Sekolah Penggerak” (PSP) in 2021 at SDN 23 Menyumbung, Sintang Regency. The research method used is a qualitative study in the form of school ethnographic research. The subjects of this study were principals, teachers, students and representatives of parents of students at SDN 23 Mengumbung. Data collection techniques in the form of observation, interviews and document studies. Data collection tools in the form of observation guidelines, interview guidelines and supporting documents. Data analysis techniques are data reduction, data presentation and conclusion drawing. The results of the study show that: 1) the leadership competence of principals has increased in terms of designing policy directions, managing human resources, designing school budgets and building partnerships with stakeholders after PSP intervention; 2) There is an adaptation to changes in teacher performance in the learning process, namely the teacher guides students more intensively in class and uses media so that students understand the material more easily; 3) Several internal factors that support the initial change in the implementation of PSP at SDN 23 Contributing, namely: the attitude, commitment and managerial competence of the principal, the teacher's performance and positive response to changes in education policy, parental support through the school committee, and school conditions that can relate to electricity and internet network. Meanwhile, external factors are the socio-economic-cultural conditions of the community, support from industry and local government and support for local government policies.